Community Perceptions in Resolving Ikhtilaf and Its Relevance to Surah An-Nisa’ Verse 59 in Ceurih Village of Ulee Kareng District, Banda Aceh - Almuyassar, Faris (TAFSE: Journal of Qur'anic Studies, 2023)
Ikhtilaf is differences of opinions in understanding a matter, but not everyone can accept those differences in navigating social life. In this case, some residents of Ceurih community in Aceh can accept the occurrence of ikhtilaf, while others might find it challenging and even reject it although ideally ikhtilaf must be accepted as explained in surah An-Nisa verse 59. Based on this issue, the researcher aimed to examine the community’s understanding in resolving the problem of ikhtilaf among them so far. This study was conducted using a qualitative method with field research as a means of data collection. The data were analyzed using descriptive qualitative analysis generating descriptive data in the forms of people’s words or oral and observable behaviors. The results show that there were two understandings of resolving ikhtilaf. Some people within the society agreed with the village head’s decisions to resolve disagreements as mentioned in surah An-Nisa verse 59 that it is obligatory to follow ulil amr (the leader) as long as it does not contradict with Al-Quran and Sunnah. However, others dealt with ikhtilaf by making their personal decision without consulting their leader. Therefore, not all members of the community in Ceurih village implemented the essence of surah An-Nisa verse 59 in resolving the occurrence of ikhtilaf.